THE DOCTRINE OF ANTI-VIOLENCE IN RELIGION: A COMPARISON STUDY OF THE SCRIPTURES OF RELIGIONS IN INDONESIA - El-Hakim, Atraf Husein; Idlofi, Idlofi; Hamid, Abdur Rahman Nor Afif (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2022)
Religion spread in this universe is a symbol for a person in dealing with fellow humans and other living creatures. Religious teachings teach their adherents to have compassion and care for one another; there is no single religion that instructs its adherents to commit violence and even kills creatures. This article describes the religious doctrines of non-violence and their similarities and differences. Then we will look at the manifestation of the non-violence doctrine in the adherents of each religion. As a methodical step, this research uses a qualitative method with a library research approach with a content analysis knife. This research concludes that all teachings brought by religious scriptures in Indonesia have the principle of promoting love for others. However, under certain conditions, it turns out that the teachings of the scriptures also provide the freedom to take decisive actions. However, in conditions of peace, no one is advocating for decisive action. When some of the congregation carry out strict teachings, then it is a person who misunderstands in understanding the holy book.